False positive detection rate of R2-CAD in evaluation of breast lesions at Full-Field-Digital Mammogram (FFDM) - Hassan, Radhiana; Samad Cheung, Humairah; Abdul Rashid, Mohd Amran; Che Mohamed, Siti Kamariah; Y, Fitrina Yusrin (2009)
Introduction: Interpretation of mammogram is a challenging task and the performance level of readers is known to vary widely between general radiologist and breast imaging experts. R2-CAD is a software-based system to identify regions of the mammogram with suspicious features and to draw the reader’s attention to these areas and decide whether they are genuinely abnormal. It has been available for several years with FDA Approval and was recently brought to our centre with the use of FFDM.